Parental Knowledge Attitudes and Practice Towards Headaches Among Elementary School-Aged Children in Al-Baha, Saudi Arabia - M. Alzahrani, Mohammed Hassan; Alghamdi, Abdullah S.; A. Al Shaikh, Mohammed Ibrahim; M. Alghamdi, Waleed Saeed; M. Alghamdi, Adel Abdulrhman; M. Alghamdi, Ziyad Farouq; M. Alghamdi, Rayan Tawfiq; M. Salih, Elfatih Mirghani; Alamr, Fahad Ali; Aburaida, Omer M.; A. Mohammed, Khalid Alawad (International Journal of Child Health and Nutrition, 2025)
Aim: To evaluate parental knowledge, attitudes, and practices regarding childhood headaches in Al-Baha, Saudi Arabia, and identify gaps that could inform targeted educational interventions. Methods: A cross-sectional online survey was administered to 399 parents residing in Al-Baha. The survey assessed parental understanding, behavior, and perceptions concerning pediatric headaches. Data analysis was conducted using SPSS version 27.0, applying descriptive statistics, Mann–Whitney U, Kruskal–Wallis, and Spearman’s correlation tests. Results: Among the respondents, 52.4% were female (N = 209) and 47.6% male (N = 190), with a mean age of 42.56 years. Female participants exhibited significantly higher knowledge scores than their male counterparts. The most frequently reported headache triggers were sleep disturbances (79.4%), vision problems (61.7%), and psychological factors (52.1%), whereas malnutrition was identified by only 48.9% of respondents. Symptom monitoring practices varied: 46.1% of parents reported observing symptoms before seeking medical care, while 23.0% considered headaches an emergency. Notably, 57.4% sought professional consultation when symptoms persisted, yet 32.1% administered painkillers without medical advice. Knowledge scores were positively correlated with both attitude scores (r = 0.151, p = 0.002) and practice scores (r = 0.336, p < 0.001). Conclusion: The findings indicate that parental understanding of childhood headaches is often limited, particularly concerning nutritional triggers and evidence-based management strategies. This underscores the urgent need for targeted educational initiatives to enhance awareness, promote appropriate health-seeking behavior, and reduce the risk of mismanagement.